First description of the larva of Archineura incarnata (Karsch, 1891) with notes on the biology (Odonata: Calopterygidae) - Yang, Guo-Hui; Orr, Albert G.; Zhang, Hao-Miao (Zootaxa, 2022)
The final instar larva of the genus Archineura Kirby, 1894 is described for the first time, based on a specimen of the Chinese endemic species Archineura incarnata (Karsch, 1892) collected from Mt. Nankunshan, Guangdong Province, China. The larva is distinguished by several characters, including its moderately slender build combined with the distinctive extremely long legs, long, narrow, uniquely spined outer caudal appendages, a mask strongly expanded anteriorly with a relatively small median cleft, and robust spines at the apex of the labial palp. The mask is most similar to larvae of Echo Selys, 1853, Mnais Selys, 1853 and Psolodesmus MacLachlan, 1870 which are considered its nearest relatives based on molecular analysis, but from which it differs in other characters. The biology of Archineura larvae is discussed briefly.